Healthcare People Management - Preparing today’s professionals for tomorrow - Nascimento, G.; Duarte, A. (HealthManagement.org – The Journal, 2021)
Recent paradigmatic shifts in society as a whole and healthcare in particular demand organisations to change how they approach, devise and implement their management strategies. In this context, people management is one of the priority areas, and a team of experts suggest a management model underpinning the New Health Staff 2030 context.